DAPK1 loss triggers tumor invasion in colorectal tumor cells - Steinmann, Sara; Kunze, Philipp; Hampel, Chuanpit; Eckstein, Markus; Bertram Bramsen, Jesper; Muenzner, Julienne K.; Carlé, Birgitta-Elisabeth; Ndreshkjana, Benardina; Kemenes, Stephan; Gasparini, Pierluigi; Friedrich, Oliver; Andersen, Claus; et al. (Cell Death & Disease, 2019)
Colorectal cancer (CRC) is one of the leading cancer-related causes of death worldwide. Despite the improvement of surgical and chemotherapeutic treatments, as of yet, the disease has not been overcome due to metastasis to distant organs. Hence, it is of great relevance to understand the mechanisms responsible for metastasis initiation and progression and to identify novel metastatic markers for a higher chance of preventing the metastatic disease. The Death-associated protein kinase 1 (DAPK1), recently, has been shown to be a potential candidate for regulating metastasis in CRC. Hence, the aim of the study was to investigate the impact of DAPK1 protein on CRC aggressiveness. Using CRISPR/Cas9 technology, we generated DAPK1-deficient HCT116 monoclonal cell lines and characterized their knockout phenotype in vitro and in vivo. We show that loss of DAPK1 implemented changes in growth pattern and enhanced tumor budding in vivo in the chorioallantoic membrane (CAM) model. Further, we observed more tumor cell dissemination into chicken embryo organs and increased invasion capacity using rat brain 3D in vitro model. The novel identified DAPK1-loss gene expression signature showed a stroma typical pattern and was associated with a gained ability for remodeling the extracellular matrix. Finally, we suggest the DAPK1-ERK1 signaling axis being involved in metastatic progression of CRC. Our results highlight DAPK1 as an anti-metastatic player in CRC and suggest DAPK1 as a potential predictive biomarker for this cancer type.
CRIS-Team Scopus Importer:2019-12-10

Inhibiting Interleukin 36 Receptor Signaling Reduces Fibrosis in Mice with Chronic Intestinal Inflammation - Scheibe, Kristina; Kersten, Christina; Schmied, Anabel; Vieth, Michael; Primbs, Tatjana; Carlé, Birgitta-Elisabeth; Knieling, Ferdinand; Claussen, Jing; Klimowicz, Alexander C.; Zheng, Jie; Baum, Patrick; Meyer, Sebastian; et al. (Gastroenterology, 2018)
BACKGROUND & AIMS: Intestinal fibrosis is a long-term complication in inflammatory bowel diseases (IBD) frequently resulting in functional damage, bowel obstruction, and surgery. Interleukin 36 (IL36) is a group of cytokines in the IL1 family with inflammatory effects. We studied expression of IL36 and its receptor, interleukin 1 receptor like 2 (IL1RL2 or IL36R) in development of intestinal fibrosis in human tissues and mice. METHODS: We obtained intestinal tissues from 92 patients with Crohn´s disease (CD), 48 patients with ulcerative colitis (UC), and 26 patients without inflammatory bowel diseases (controls). Tissues were analyzed by histology to detect fibrosis and immunohistochemistry to determine the distribution of fibroblasts and levels of IL36R ligands. Human and mouse fibroblasts were incubated with IL36 or control medium, and transcriptome-wide RNA sequences were analyzed. Mice were given neutralizing antibodies against IL36R and we studied intestinal tissues from Il1rl2-/- mice; colitis and fibrosis was induced in mice by repetitive administration of DSS or TNBS. Bone marrow cells were transplanted from Il1rl2-/- to irradiated wild-type mice and intestinal tissues were analyzed. Antibodies against IL36R were applied to mice with established chronic colitis and fibrosis and intestinal tissues were studied. RESULTS: Mucosal and submucosal tissues from patients with CD or UC had higher levels of collagens including type VI collagen compared to tissues from controls. In tissues from patients with fibrostenotic CD, significantly higher levels of IL36A were noted, which correlated with high numbers of activated fibroblasts that expressed alpha smooth muscle actin. IL36R activation of mouse and human fibroblasts resulted in expression of genes that regulate fibrosis and tissue remodeling, as well as expression of collagen type VI. Il1rl2-/- mice and mice given injections of an antibody against IL36R developed less severe colitis and fibrosis following administration of DSS or TNBS, but bone marrow cells from Il1rl2-/- mice did not prevent induction of colitis and fibrosis. Injection of antibodies against IL36R significantly reduced established fibrosis in mice with chronic intestinal inflammation. CONCLUSION: We found higher levels of IL36A in fibrotic intestinal tissues from patients with IBD, compared with controls. IL36 induced expression of genes that regulate fibrogenesis in fibroblasts. Inhibition or knockout of the IL36R in mice reduces chronic colitis and intestinal fibrosis. Agents designed to block IL36R signaling could be developed for prevention and treatment of intestinal fibrosis in patients with IBD.
EVALuna2:35123

Inhibiting PGGT1B Disrupts Function of RHOA, Resulting in T-cell Expression of Integrin α4β7 and Development of Colitis in Mice - Lopez Posadas, Rocío; Fastancz, Petra; Martínez-Sánchez, Luz del Carmen; Panteleev-Ivlev, Julia; Thonn, Veronika; Kisseleva, Tatyana; Becker, Lukas S.; Schulz-Kuhnt, Anja; Zundler, Sebastian; Wirtz, Stefan; Atreya, Raja; Carlé, Birgitta-Elisabeth; et al. (Gastroenterology, 2019)
Background & Aims: It is not clear how regulation of T-cell function is altered during development of inflammatory bowel diseases (IBD). We studied the mechanisms by which geranylgeranyltransferase-mediated prenylation controls T-cell localization to the intestine and chronic inflammation. Methods: We generated mice with T-cell–specific disruption of the geranylgeranyltransferase type I, beta subunit gene (Pggt1b), called Pggt1bΔCD4 mice, or the ras homolog family member A gene (Rhoa), called RhoaΔCD4 mice. We also studied mice with knockout of CDC42 or RAC1 and wild-type mice (controls). Intestinal tissues were analyzed by histology, multiphoton and confocal microscopy, and real-time polymerase chain reaction. Activation of CDC42, RAC1, and RHOA were measured with G-LISA, cell fractionation, and immunoblots. T cells and lamina propria mononuclear cells from mice were analyzed by flow cytometry or transferred to Rag1–/– mice. Mice were given injections of antibodies against integrin alpha4beta7 or gavaged with the RORC antagonist GSK805. We obtained peripheral blood and intestinal tissue samples from patients with and without IBD and analyzed them by flow cytometry. Results: Pggt1bΔCD4 mice developed spontaneous colitis, characterized by thickening of the intestinal wall, edema, fibrosis, accumulation of T cells in the colon, and increased expression of inflammatory cytokines. Compared with control CD4+ T cells, PGGT1B-deficient CD4+ T cells expressed significantly higher levels of integrin alpha4beta7, which regulates their localization to the intestine. Inflammation induced by transfer of PGGT1B-deficient CD4+ T cells to Rag1–/– mice was blocked by injection of an antibody against integrin alpha4beta7. Lamina propria of Pggt1bΔCD4 mice had increased numbers of CD4+ T cells that expressed RORC and higher levels of cytokines produced by T-helper 17 cells (granulocyte-macrophage colony-stimulating factor, interleukin [IL]17A, IL17F, IL22, and tumor necrosis factor [TNF]). The RORC inverse agonist GSK805, but not antibodies against IL17A or IL17F, prevented colitis in Pggt1bΔCD4 mice. PGGT1B-deficient CD4+ T cells had decreased activation of RHOA. RhoAΔCD4 mice had a similar phenotype to Pggt1bΔCD4 mice, including development of colitis, increased numbers of CD4+ T cells in colon, increased expression of integrin alpha4beta7 by CD4+ T cells, and increased levels of IL17A and other inflammatory cytokines in lamina propria. T cells isolated from intestinal tissues from patients with IBD had significantly lower levels of PGGT1B than tissues from individuals without IBD. Conclusion: Loss of PGGT1B from T cells in mice impairs RHOA function, increasing CD4+ T-cell expression of integrin alpha4beta7 and localization to colon, resulting in increased expression of inflammatory cytokines and colitis. T cells isolated from gut tissues from patients with IBD have lower levels of PGGT1B than tissues from patients without IBD.
CRIS-Team Scopus Importer:2019-10-08
Keywords: IBD; Immune Regulation; Mouse Models; Prenylation

Label-Free Characterization and Quantification of Mucosal Inflammation in Common Murine Colitis Models With Multiphoton Imaging - Kreiß, Lucas; Thoma, Oana-Maria; Lemire, Sarah; Lechner, Kristina; Carlé, Birgitta-Elisabeth; Dilipkumar, Ashwathama; Kunert, Timo; Scheibe, Kristina; Heichler, Christina; Merten, Anna-Lena; Weigmann, Benno; Neufert, Clemens; et al. (Inflammatory Bowel Diseases, 2022)
Background Clinical challenges in inflammatory bowel diseases require microscopic in vivo evaluation of inflammation. Here, label-free imaging holds great potential, and recently, our group demonstrated the advantage of using in vivo multiphoton endomicroscopy for longitudinal animal studies. This article extends our previous work by in-depth analysis of label-free tissue features in common colitis models quantified by the multiphoton colitis score (MCS). Methods Fresh mucosal tissues were evaluated from acute and chronic dextran sulfate sodium (DSS), TNBS, oxazolone, and transfer colitis. Label-free imaging was performed by using second harmonic generation and natural autofluorescence. Morphological changes in mucosal crypts, collagen fibers, and cellularity in the stroma were analyzed and graded. Results Our approach discriminated between healthy (mean MCS = 2.5) and inflamed tissue (mean MCS > 5) in all models, and the MCS was validated by hematoxylin and eosin scoring of the same samples (85.2% agreement). Moreover, specific characteristics of each phenotype were identified. While TNBS, oxazolone, and transfer colitis showed high cellularity in stroma, epithelial damage seemed specific for chronic, acute DSS and transfer colitis. Crypt deformations were mostly observed in acute DSS. Conclusions Quantification of label-free imaging is promising for in vivo endoscopy. In the future, this could be valuable for monitoring of inflammatory pathways in murine models, which is highly relevant for the development of new inflammatory bowel disease therapeutics.
CRIS-Team WoS Importer:2022-10-07

Label-Free In Vivo Histopathology of Experimental Colitis via 3-Channel Multiphoton Endomicroscopy - Kreiß, Lucas; Thoma, Oana Maria; Dilipkumar, Ashwathama; Carlé, Birgitta-Elisabeth; Longequeue, Pascal; Kunert, Timo; Rath, Timo; Hildner, Kai; Neufert, Clemens; Neurath, Markus; Friedrich, Oliver; Schürmann, Sebastian; et al. (Gastroenterology, 2020)
CRIS-Team Scopus Importer:2020-08-28

Label-Free Multiphoton Endomicroscopy for Minimally Invasive In Vivo Imaging - Dilipkumar, Ashwathama; Al-Shemmary, Alaa; Kreiß, Lucas; Cvecek, Kristian; Carlé, Birgitta-Elisabeth; Knieling, Ferdinand; Menezes, Jean Gonzales; Thoma, Oana-Maria; Schmidt, Michael; Neurath, Markus; Waldner, Maximilian; Friedrich, Oliver; et al. (Advanced Science, 2019)
Multiphoton microscopy of cellular autofluorescence and second harmonic generation from collagen facilitates imaging of living cells and tissues without the need for additional fluorescent labels. Here, a compact multiphoton endomicroscope for label-free in vivo imaging in small animals via side-viewing needle objectives is presented. Minimal invasive imaging at cellular resolution is performed in colonoscopy of mice without surgical measures and without fluorescent dyes as a contrast agent. The colon mucosa is imaged repeatedly in the same animal in a mouse model of acute intestinal inflammation to study the process of inflammation at the tissue level within a time period of ten days, demonstrating the capabilities of label-free endomicroscopy for longitudinal studies for the first time.
CRIS-Team Scopus Importer:2019-05-02
Keywords: endoscopy; inflammatory bowel disease; multiphoton microscopy; optical imaging

Raster-Scanning Optoacoustic Mesoscopy for Gastrointestinal Imaging at High Resolution - Knieling, Ferdinand; Menezes, Jean Gonzales; Claussen, Jing; Schwarz, Mathias; Neufert, Clemens; Fahlbusch, Fabian B.; Rath, Timo; Thoma, Oana-Maria; Kramer, Viktoria; Menchicchi, Bianca; Kersten, Christina; Scheibe, Kristina; et al. (Gastroenterology, 2018)
EVALuna2:33792